Supervisors’ Perceptions of Postgraduate Students’ Thesis Literature Review Writing in a Ghanaian University - Afful, Joseph Benjamin Archibald; Ngula, Richmond S.; Twumasi, Rita; Tetteh, Gabriel; Mensah, Frank (Advances in Social Sciences Research Journal, 2022)
A key rhetorical unit in the thesis, the literature review has in recent times received some interest by specialists and researchers of English for Academic Purposes, academic literacy, discourse analysis, and assessment. The present study reports the perceptions of graduate supervisors regarding students’ engagement with thesis literature review writing, focusing on students’ challenges and strategies faced and adopted respectively. Semi-structured interviews were administered to nine (three each) supervisors from three Humanities departments from one public Ghanaian university. The results showed, first, supervisors’ awareness of thesis literature review writing as pivotal and, second, challenges such as reading and comprehension of texts, exercising criticality, synthesizing, referencing, and language use. Further, supervisors identified graduate students’ key coping strategies such as summarizing, paraphrasing, patchwriting, concept mapping, and guidelines from supervisory interactions. These findings have implications for the scholarship on supervisors’ perceptions concerning postgraduate students’ literature review writing in a region least featured in the literature as well as postgraduate pedagogy and further research.